Clinical Legal Education: An Examination of the Pedagogy of the Nigerian Law School and The Evaluation System - Yakusak Aduak (The Indonesian Journal of International Clinical Legal Education, 2022)
The Nigerian Law School is a vocational training institution, a finishing school for those who aspire to practice in the Nigerian Bar. The training is centered on procedural law, lawyering skills, and trial advocacy. To deliver that, the Institution keeps reviewing its curriculum to achieve its objectives. Presently, the curriculum is sandwiched in a nine (9) month program which includes about 20 weeks of orientation and lectures, 2 weeks of mock trials, 10 weeks of externships under Court and Law Office placements, 3 weeks of evaluation which includes the portfolio assessment of activities done or experienced during the externship period and final exams. The final examination at the Nigerian Law School is scenario-based Multiple Choice Questions (MCQ) and essay questions which form part of the final score and grade of a candidate. Students' externship activities are evaluated through the portfolio assessment exercise with a pass mark of 70%. Students who do not pass the portfolio assessment will not be called to the Nigerian Bar and will be required to repeat the externship exercise, but the score earned does not form part of the final marks for grading. It was found that as a result of the non-inclusion of mock trials and portfolio assessment in the final score of the students, many of the students do not show much commitment to the activities and as such miss out on the simulations and experiential learning that are key in preparing them for practice. It was also discovered that one of the challenges of including the scores of exercises like portfolio assessment and mock trials into the final score, is the integrity of the process. However, in clinical legal education, such activities need to be part of the final score.